Stem Cells, Biotechnology, and Human Rights: Implications for a Posthuman Future - Lauritzen, Paul (The Hastings Center report, 2005)
If stem cell research led to therapies that changed the natural contours of human life, it would unsettle our ethical commitments, including the very notion of a human right, and encourage us to see the entire natural world, the human body along with it, as having the status only of material to be manipulated.